Self Concept And Competence Influence Organizational Commitment And Its Implications On Employee Performance - Saragih, Nedire; Sammary, Merry (Journal Boas : Business, Economics, Accounting And Management, 2024)
From the initial research that researchers did, the weakness of employees in building confidence (building trust), namely interaction with other individuals and building a sense of confidence in the company. Concerns and feelings of uncertainty that cause employee commitment to be disrupted, in addition to the result of not being able to focus time and effort on tasks and jobs that result in neglected aspects of work, also because there are still employees who have not been able to accept responsibilities from the work of others positive or negative, this is because there are still employees who have not been able to develop a criteria or work procedures to achieve the quality, productivity and work services needed. The purpose of this study was to determine the effect of self-concept and competence on organizational commitment and its implications for employee performance. The number of samples in this study amounted to 93 people using saturated sample techniques. The analysis technique used is multiple linear regression. The results showed that there was no direct influence of the significance of self-concept on organizational commitment. Directly there is a significant influence of competence on organizational commitment. There is a direct influence of the significance of self-concept on employee performance. There is no direct influence of competency significance on employee performance. Directly there is a significant influence of organizational commitment on employee performance. Indirectly X1 through Y has a significant effect on Z. Indirectly X2 through Y has a significant influence on Z.